Solidarity and the problem of structural injustice in healthcare. (25th July 2018) - Gould, Carol C.
Abstract: The concept of solidarity has recently come to prominence in the healthcare literature, addressing the motivation for taking seriously the shared vulnerabilities and medical needs of compatriots and for acting to help them meet these needs. In a recent book, Prainsack and Buyx take solidarity as a commitment to bear costs to assist others regarded as similar, with implications for governing health databases, personalized medicine, and organ donation. More broadly, solidarity has been understood normatively to call for 'standing with' or assisting fellow community members and possibly also distant others in regard to their needs, whether for its own sake or in order to realize the demands of justice. I argue here that the understanding of solidarity in the existing bioethics literature is unduly restricted by not sufficiently theorizing the notion of structural (or systemic) injustice and its import for understanding solidarity. Extending traditional conceptions of labor and social movement solidarity, I contrast unitary solidarity within a given group with 'networking solidarities' across groups. I analyze the meaning of structural injustice and its significance for solidarity, including countering institutionally entrenched inequalities and economic exploitation. I then apply this broadened conception to healthcare, discussing structural problems with the U.S. insurance system and the solidarity movements addressing its deficiencies. I analyze some natural disasters and global health challenges that were aggravated by structural injustices, along with the solidarity movements they engendered. Finally, I revisit the questions of governing health databases and of personalized medicine with the enlarged conception of solidarity in view.